Unique dental arrangement in a new species, Groenlandaspis howittensis (Placodermi, Arthrodira) from the Middle Devonian of Mount Howitt, Victoria, Australia. - Austin N. Fitzpatrick; Alice M. Clement; John A. Long (PeerJ)
Well-preserved specimens of a new species of arthrodiran placoderm, Groenlandaspis howittensis sp. nov. (Middle Devonian of Victoria, Australia), reveals previously unknown information on the dermal skeleton, body-shape and dentition of the wide-spread genus Groenlandaspis. The new material includes dual pineal plates, extrascapular plates, and cheek bones showing the presence of cutaneous sensory organs. The anterior supragnathal, usually a paired element in arthrodires, is a fused median bone in G. howittensis sp. nov. It is positioned anterior to the occlusion of the mouth between the lower jaw (infragnathals) and upper jaw (posterior supragnathals) bones, indicating a specialised feeding mechanism and broadening the known diversity of placoderm dental morphologies. G. howittensis sp. nov. differs from all other groenlandaspidids by a less pronounced posterior expansion of the nuchal plate; the shape of the posterior dorsolateral plate and the presence of a short accessory canal on the anterior dorsolateral plate. A new phylogenetic analysis positions Groenlandaspididae in a monophyly with the phlyctaeniid families Arctolepidae and Arctaspididae, however, the specific intrarelationships of groenlandaspidids remain poorly resolved.